Sedentary behaviour and physical inactivity assessment in primary care: the Rapid Assessment Disuse Index (RADI) study. Issue 3 (21st October 2013) - Shuval, Kerem; Kohl, Harold W; Bernstein, Ira; Cheng, Dunlei; Pettee Gabriel, Kelley; Barlow, Carolyn E; Yinghui, Liu; DiPietro, Loretta
Abstract : Background: The emerging evidence of the effects of sedentary time on health outcomes suggests a need to better measure this exposure. Healthcare settings, however, are not equipped with a tool that can quickly assess the sedentary habits of their patient population. The purpose of this study was to validate a tool for rapidly quantifying and tracking the sedentary time and low levels of daily lifestyle physical activity among primary care patients. Methods: The study examined the test–retest reliability and validity of the rapid assessment disuse index (RADI) among adult patients from a large primary care clinic. Patients completed RADI (comprised of 3 items: sitting, moving and stair climbing) twice, followed by accelerometer monitoring. Test–retest reliability was computed, and the correlation between survey responses and accelerometry was determined. A receiver operating characteristic curve was constructed and the area under the curve (AUC) was calculated. Results: RADI was temporally stable (intraclass correlation coefficients 0.79), and a higher score was significantly correlated with greater sedentary time (ρ=0.40; p<0.01), fewer sedentary to active transitions (ρ=−0.42; p<0.01), and less light-intensity physical activity (ρ=−0.40; p<0.01). The ability of RADI to detect patients with high levels of sedentary time was fair (AUC=0.72). Conclusions: This brief assessment tool, designed to quickly identify patients with high levels of sitting and low daily physical activity, exhibits good reliability and moderate validity. RADI can assist in providing recommendations at the point of care pertaining to modifying sedentary behaviour.